FENOMENA MASYARAKAT BAHASA PADA PRODI PENDIDIKAN BAHASA DAN SASTRA KELAS C ANGKATAN 2020 - Alda Octaviena Putri; Titik Indarti; Resdianto Permata Raharjo (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2022)
This research is motivated by the phenomenon of the use of everyday language used in Class C Education or PC. Based on the data sources, what will be studied are Indonesian Language and Literature Education students for the 2020 class PC class at UNESA who come from several regions, with the language used as reference material. In this paper, it is found that PC students have different languages in each area where they live. This condition will bring up one type of language used to communicate. The author uses a qualitative method by using survey data collection. The results obtained by the author are that PC class students use Javanese to communicate in their daily life. Keywords: Sociolinguistics, Language, Language Society